2021
DOI: 10.1111/acel.13439
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation‐based biomarkers of aging were slowed down in a two‐year diet and physical activity intervention trial: the DAMA study

Abstract: Several biomarkers of healthy aging have been proposed in recent years, including the epigenetic clocks, based on DNA methylation (DNAm) measures, which are getting increasingly accurate in predicting the individual biological age. The recently developed “next‐generation clock” DNAmGrimAge outperforms “first‐generation clocks” in predicting longevity and the onset of many age‐related pathological conditions and diseases. Additionally, the total number of stochastic epigenetic mutations (SEMs), also known as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 68 publications
(70 reference statements)
2
65
0
Order By: Relevance
“…In fact, childhood traumas have been associatedwith a high risk of alcoholism, smoking, physical inactivity, and severe obesity [30]. Several studies have demonstrated that adherence to a healthy lifestyle may slow phenotypic aging [31][32][33][34][35]. This confirms our hypothesis, childhood traumas → unhealthy lifestyle → accelerated phenotypic aging.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, childhood traumas have been associatedwith a high risk of alcoholism, smoking, physical inactivity, and severe obesity [30]. Several studies have demonstrated that adherence to a healthy lifestyle may slow phenotypic aging [31][32][33][34][35]. This confirms our hypothesis, childhood traumas → unhealthy lifestyle → accelerated phenotypic aging.…”
Section: Discussionsupporting
confidence: 85%
“…Here, the intervention cohort showed a 3.23 year age reversal. These findings have been corroborated in a larger 2-year study on 219 women subjected to diet and exercise where the intervention group showed significant reduction in a marker of DNA methylation age (Fiorito et al, 2021). Clearly, these prospective trials show that epigenetic markers of aging can indeed be reversed.…”
Section: Exercisementioning
confidence: 67%
“…In contrast to (poly-)genetic risk scores that are set at birth, the epigenetic clock changes throughout life. We and others have shown that these changes are potentially sensitive to interventions [47][48][49][50][51] and lifestyle factors [37]. Whether this is true for diabetes specific interventions needs to be examined in sufficiently sized longitudinal studies.…”
Section: Discussionmentioning
confidence: 97%